THE INFLUENCE OF ORGANIZATIONAL CULTURE ON EMPLOYEE QUALITY MEDIATED BY WORK MOTIVATION - Nur M. Ridha Tarigan; Abd. Rasyid; Ahmad Husin Lubis (Management and Sustainable Development Journal, 2026)
The low quality of a state institution can impact a poor service system. This is because it can be influenced by internal or external factors from the institution itself. This study aims to examine the influence of organizational culture on Employee Quality with work motivation as a mediator. This study was conducted in the Karo Regency government. The data collection method used a quantitative approach. Respondents who returned the questionnaire were 202 people. The data analysis method used Structural Equation Modeling (SEM) using SmartPLS software. The results explain that organizational culture has a positive effect on work motivation. Furthermore, organizational culture also has a positive effect on Employee Quality, as well as work motivation which has a positive effect on Employee Quality, and organizational culture has a positive effect on Employee Quality through work motivation in Karo Regency